Phylogenetic position and systematics of the bryozoan Tennysonia: further evidence for convergence and plasticity in skeletal morphology among cyclostome bryozoans - Taylor, Paul D.; Waeschenbach, Andrea; Florence, Wayne K. (Zootaxa, 2011)
Cyclostomes are an ancient order of marine bryozoans with a fossil record extending back over 450 million years into the Ordovician. The current taxonomy of both fossil and modern cyclostomes is based almost entirely on skeletal characters but newly available sequence data are beginning to reveal rampant convergence of some of them. An unusual combination of skeletal characters in the South African cyclostome Tennysonia stellata Busk, 1867 has made this genus difficult to classify. After revising the taxonomy of Tennysonia, we use almost complete small and large ribosomal subunits (ssrDNA and lsrDNA) to demonstrate its close phylogenetic affinity with the tubuliporine genus Idmidronea (family Tubuliporidae) with which it shares a similar colony form, despite the presence of skeletally open kenozooids between the autozooids, reminiscent of cerioporine cyclostomes such as Favosipora. The spaces between the transverse rows of autozooidal apertures, occupied by exterior autozooidal frontal walls in Idmidronea, are occupied by kenozooids in Tennysonia, thereby maintaining the spacing between lophophores necessary for efficient suspension feeding. Sympatric colonies of T. stellata with narrow and broad branches are identical or almost identical on the basis of ssrDNA and lsrDNA sequences, respectively, suggesting within-species ecophenotypic plasticity in this aspect of colony form.